The Correlation Between Risk Factors and The Incidence of Traumatic Cataract Due to Blunt Trauma In Soetomo General Hospital Surabaya April 2017 – March 2020 - Faiqoh, Maimanah Zumaro Ummi; Wahyuni, Indri; Umijati, Sri; Hermawan, Dicky (Syntax Literate, 2021)
Backgrounds: Cataract is the cause of 51% of blindness in the world. Cataracts can be caused by eye trauma, where 55 million eye trauma incidences are recorded annually. The most common trauma is blunt trauma. Based on previous studies, there were different research results on risk factors for eye trauma, and there were still few studies on traumatic cataracts due to blunt trauma. This study aims to determine the correlation between risk factors and the incidence of traumatic cataracts due to blunt trauma. Methods: This study is an analytical study with a cross-sectional approach. The sampling technique used is total sampling with 52 samples of traumatic cataract patients in Dr. Soetomo General Hospital. The independent variables are the risk factors for age, gender, type of work, and location of trauma. The dependent variable is the incidence of traumatic cataracts due to blunt trauma. The data was collected with medical records and were analyzed using the chi-square test. Results: A total of 21 patients (40.4%) had traumatic cataracts due to blunt trauma, and 31 patients (59.6%) had traumatic cataracts due to other trauma. The significance value of the correlation between age, gender, type of work, and location of trauma with the incidence of traumatic cataract due to blunt trauma respectively p=0.557, p=0.675, p=0.198, and p=0.512, which means p >0.05, so there is no significant correlation. Conclusion: There is no correlation between the risk factors and traumatic cataracts due to blunt trauma